Islamic Boarding Schools as a Solution to Child Violence: A Holistic Approach to Character Education : Islamic Boarding Schools as a Solution to Child Violence: A Holistic Approach to Character Education - Siti Qomala Khayati (Cv. Kayaswara, Indonesia, 2025)
Child violence is a persistent and escalating issue across various regions of Indonesia, with physical, verbal, and psychological abuse inflicting long-term negative impacts on children's development. In this challenging context, Islamic boarding schools (pondok pesantren), as religious-based educational institutions, hold significant potential as both preventive and curative solutions to this societal problem. This research explores the pivotal role of pondok pesantren in fostering strong spiritual, emotional, and social character in children, alongside the proactive efforts these institutions undertake to cultivate a safe and nurturing environment. Employing a qualitative research methodology with a case study approach across several pondok pesantren in East Java, the findings reveal several key factors. Intensive instruction in religious values, structured discipline, and close-knit relationships among students, teachers, and caregivers are instrumental in preventing violence and promoting positive character development in children. Consequently, pondok pesantren emerge as a viable alternative educational model that can significantly contribute to the reduction of child violence, particularly within non-formal education settings rooted in strong values.